Peran Pemerintah dalam Stabilitas Ekonomi Pasar - Indra Hidayatullah (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
The role of government interference in controlling the economy of a market. The function of the government as a bumper. They may collude to destroy the natural mechanism of free markets in their interests at the expense of the interests of others or common interests. They can even crush each other. In the framework of the ideal model the function of the government is indeed minimal. But at the same time the government has a duty to reduce and even eliminate practices that lead to monopolies and privileges due to the detriment of others. The role of government in the market economy depends on developing market conditions. When the market is normal in its economic turnaround, the government functions as a supervisor in the market so that practices that do not deviate from existing market theory concepts do not occur. Another way that is done by the government is to make laws about goods or services that are urgent for the community to be controlled by the state, so that the goods cannot be monopolized by one or group. By being free in the market economy, the government must intervene so that stability the market economy can be controlled and in accordance with all expectations of market participants.